Habitat type and macroinvertebrate assemblages in low order Patagonian streams - Velásquez, Stella Maris (2003)
Benthic macroinvertebrate community structure was studied with respect to stream habitat type in four low-order Patagonian streams (Argentina). Seven habitat types were sampled during high and low water periods in each river. Boulders, cobbles, pebbles and gravels were sampled in run/riffle sections, whereas sand, leaf packs and macrophytes were sampled in pools. Run-riffles supported higher densities and biomasses of invertebrates than sand in pools but had densities similar to those in macrophytes. Benthic organic matter was highest in leaf packs in pools (4.21g DM/ 0.1m2) and was composed of leaf fragments, wood and entire leaves. The dry weight of organic matter among boulders, cobbles and pebbles in riffles areas ranged from 0.69 to 0.85g DM/0.1m2. Detrended correspondence analysis showed that species assemblages differed seasonally, and that species associations differed markedly among substrata and rivers. Proportions of five functional feeding groups differed among habitats, although gatherers were dominant in most habitat types. Shredders and collectorgatherers co-dominated numerically in leaf packs but shredder biomass was highest among boulders and gravels. Filterers were numerically dominant on macrophytes and gravels, whereas scrapers were common on all riffle substrata. At the habitat scale, current velocity, water temperature and organic matter availability appear to be major factors affecting the distribution and abundance of Patagonian stream invertebrates. Our results provide baseline data on poorly studied river systems whose integrity is threatened by sediment inputs from forestry and agriculture.